Updating the euro area Phillips curve: the slope has increased - Sami Oinonen; Maritta Paloviita (Bank of Finland, 2014)
This paper examines recent changes in the cyclicality of euro area inflation. We estimate time-varying parameters for the hybrid New Keynesian Phillips curve using three alternative proxies for the output gap. Our analysis, which is based on the state-space method with Kalman filtering techniques, suggests that the slope of the euro area Phillips curve has become steeper since 2012. Thus, the current low level of inflation and persistently negative output gap increase the risk that euro area inflation will stay below the monetary policy target for an extended period.
URN:NBN:fi:bof-201412193441
Keywords: E31; E52; E32; 330; inflation; Phillips curve; cycle